PENGARUH DURASI WAKTU TERHADAP PEMBENTUKAN PAKET CALL DATA RECORD PADA SERVING GPRS SUPPORT NODE DI P.T TELKOMSEL REGIONAL JAWA TENGAH DAN D.I. YOGYAKARTA - Wirati, Andyan Susilo; Dewanto, Wahyu (Jurnal Teknik Elektro, 2009)
SGSN (Serving GPRS Support Node) is a node which connect GSM network to GPRS network. SGSNfunctions like MSC in GSM system in monitoring MS location or mobility management, paging, datacompression, traffic calculation, charging, security and controlling data accesing prosses. SGSN is connectedbase station by using Gb interface.Data collecting in details of using GPRS service usage is needed to know how far the GPRS servicedevelopes among the customers is one of the systems used those data collecting.The population of this research is P.T Telkomsel cellular operator. The research sample is takenrandomly. Five research samples for each day in five days can be obtained. The sample taken is not based onthe used application. The research variables comprise time duration and file package.The research is conducted by quantitative methode based on the data got from P.T Telkomsel operators,then analyse toward SGSn and effect of time duration toward CDR file formation will be carried out. Theresearch data in the form of SGSN CDR output data and GPRS empirical research dat are the use of G{RS bycustomers seen from the used time duration and data volume.The result of this research will look out how far the effect of the time duration used by customers towardCDR file formation in SGSN is the research finding shows that the time duration used by customersinfluences the amount of file package formed in SGSN so that it can affect the next process. Besides, there aesome factors supporting the data sending delay technically or non technically. Another research findingshows the GPRS service quality of P.T Telkomsel bassed on the research.Based on the research results, it is suggested to do a research on charging GGSN in GPRS, chargingmechanism of each software supporting SGSN. So that the strong point of eacg software we can know.Keyword : SGSN, Duration of time, CDR